Educators’ Perceptions of AI and ChatGPT: Comfort, Ethics, and Readiness in Teaching - Khoirawati; Zaimuddin; Aidah; Sukainah; Muhammad Fairuz Fakhri; Suriati; Redi Pirmansyah (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study examines educators’ perceptions of AI, particularly ChatGPT, focusing on comfort, ethical considerations, and teaching readiness within teacher education. The study responds to the rapid integration of AI in education and the need for its responsible and pedagogically meaningful use. An explanatory sequential mixed-methods design was employed. Quantitative data were collected through an online survey of 120 in-service educators from various educational levels in Indonesia, measuring technology comfort, perceived benefits and risks of AI, personal readiness, and institutional support. To deepen the findings, qualitative data were gathered through semi-structured interviews with 20 purposively selected participants. Quantitative data were analysed using descriptive statistics, exploratory factor analysis, reliability testing, and correlation analysis, while qualitative data were analysed thematically with support from LDA topic modelling. The results show that most educators hold positive attitudes toward AI and perceive ChatGPT as useful for instructional planning, writing assistance, and feedback provision. Nevertheless, ethical concerns, particularly related to plagiarism, fairness, and student dependency, remain significant. Although educators report moderate to high personal readiness to adopt AI, institutional support in terms of clear policies, ethical guidelines, and professional development is still limited. This study underscores the importance of strengthening AI literacy, developing ethical frameworks, and enhancing institutional support to ensure the sustainable and responsible integration of AI in teacher education.